Herd Structure and Dairy Performance on Smallholder Dairy Farms in Uasin Gishu County - G. N. , Mabonga (African Journal of Education,Science and Technology (AJEST), 2018)
A cross-sectional proportional and stratified random sample survey of sixty four smallholder dairy farms in Uasin Gishu County was carried out to characterize the herd structure and determine performance. Data to elicit information on the herd structure and performance were recorded using a structured questionnaire that was developed, pre-tested and used for collecting quantitative data for the study. The results showed that the dominant improved breeds kept comprised exotic cattle-zebu crosses (62.3%), Friesian 15.3%, Ayrshire 11.6%, Guernsey 5.3%, Local 3.1% and Jerseys 2.4% with significant differences (p<0.05) in milk yields. A range recorded was 1 – 3 cows per household. The milk yield /cow/day was 27% producing between 6-8 litres with 13% and 5% of the respondents producing 11 and 12 litres of milk/cow/day respectively; 7% and 12% others producing 1-3 and 4-5 litres of milk/cow/day respectively. The results also showed the reasons of dairy farming at 53% profit, 41% hobby, 3% and 3% for household consumption and family insurance respectively. The study also ascertained experience in dairy farming at 16%, 31%, 10%, 3% and 4% at less than 5, 6-10, 11-16, 17-20 and 21 and above years respectively. The study further sought to ascertain factors such as age at first service, age at first calving, days open, calving interval, lactation length, milk yield per cow per day and method used in breeding as factors influencing herd structure and performance. This study further observed that level of education, monthly income and the size of the farm influenced herd structure and dairy performance. It is recommended that management skills, strong institutional linkages, support for commercial rearing of dairy breeding stock, and feeds diversification programme should be developed to improve performance of dairy herds in the study area.